The Quantification of Extracellular Trap Cell Death-Derived Products as Diagnostic Biomarkers for Otitis Media With Antineutrophil Cytoplasmic Antibody-Associated Vasculitis and Eosinophilic Otitis Media. Issue 3 (March 2022) - Morita, Shinya; Nakamaru, Yuji; Fukuda, Atsushi; Fujiwara, Keishi; Suzuki, Masanobu; Hoshino, Kimiko; Honma, Aya; Homma, Akihiro
Abstract : Objective: This study aimed to quantify the cell-free deoxyribonucleic acid (DNA), citrullinated-histone H3 (cit-H3)-DNA complex, and myeloperoxidase (MPO)-DNA complex as extracellular trap cell death (ETosis)-derived products in the middle ear fluid, and to identify diagnostic biomarkers for the discrimination of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (OMAAV) from eosinophilic otitis media (EOM). Study Design: Prospective study. Setting: Tertiary referral center. Patients: OMAAV patients were eligible for inclusion in this analysis. Patients with EOM were examined as controls. Intervention: All samples were obtained from the middle ear fluid in patients with OMAAV or EOM. The fluid samples were aspirated from the middle ear through the anterior-inferior portion of the tympanic membrane using a 1-ml tuberculin syringe with a 24- or 26-gauge needle under a microscope. Main Outcome Measures: The levels of cell-free DNA, cit-H3-DNA complex and MPO-DNA complex in the fluid samples were quantified using an enzyme-linked immunosorbent assay. Results: Patients with OMAAV showed significantly higher levels of MPO-DNA complex compared to patients with EOM, regardless of the serum ANCA status at the time of sampling ( p < 0.001 and p < 0.001, respectively). Meanwhile, there were no significant differences in the values of cell-free DNA or cit-H3-DNA complex between the OMAAV and EOM patients. Conclusion: The findings of this study suggest that the detection and quantification of MPO-DNA complex in the otitis media fluid can be utilized to discriminate OMAAV, especially in cases of eosinophilic granulomatosis with polyangiitis, from EOM regardless of the serum ANCA status. It should be noted that it is possible for cell-free DNA and cit-H3-DNA complex in fluid samples to be derived from dead cells other than neutrophils that undergo ETosis.